Ultrasonic shot peening advancements and their impact on alloys microstructure behavior: A concise review - Aina Najwa, Azmi; Muhammad Syamim, Mazlan; Mohamad Rusydi, Mohamad Yasin (Springer Singapore, 2024)
The mechanical properties of solid metals and alloys can be enhanced by applying ultrasonic shot peening (USP) because it results in compressive residual stress. USP has huge potential to be utilized in improving the mechanical properties and fatigue life of metallic components, hence it has recently gained much attention as a novel surface treatment technique. Shot peening uses ultrasonic vibrations at high frequencies to drive tiny spheres, or shots, into a workpiece’s surface, where they cause plastic deformation and create a compressive residual stress layer in the microstructure. The present paper provides a comprehensive overview of the principles, mechanisms, and applications of ultrasonic shot peening, highlighting its benefits over conventional shot peening techniques. The paper also discusses the research gaps and the latest advancements in the field.